Fast and inefficient star formation due to short-lived molecular clouds and rapid feedback - Kruijssen, Diederik; Chevance, Mélanie; Hygate, Alexander P. S.; Haydon, Daniel T. (Nature, 2019)
Observations that molecular gas in NGC 300 is spatially uncorrelated with high-mass stars are attributed to rapid evolution, with molecular clouds quickly destroyed by stellar feedback, and low star-formation efficiency.
Gesehen am 01.07.2019